Tworzenie w edukacji wczesnoszkolnej warunków do uczenia się przez badanie - Buła, Anna (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
Scientific reasoning and the use of research methods are universal skills that are important not only during school education, but also after it, during the whole life, whose quality is determined by cognitive attitude and the ability to cope with problematic situations. Meanwhile, already at the stage of early childhood education this area is heavily neglected. The article is a presentation of research conducted in selected Lodz kindergartens and primary schools on the possibility of scientific thinking development in children.